Impact of Structured, Systematic and Massive Violations In the General Election - Mahyudin Mahyudin; Edy Haryanto; Rahmah Marsinah (Universitas Muhammadiyah Surakarta, 2020)
Authority in resolving disputes regarding the results of general elections is the authority of the constitutional court granted by the constitution. While the authority in resolving violations is structured, systematic and massive is the authority of the electoral supervisory body granted by law. In the dispute over the results of the general election, which was decided by the constitutional court, the constitutional court did not have the authority to test the petition filed on the basis of a structured, systematic and massive violation because the constitutional court only based on the dispute over the results as intended in its authority. The court verdict has been in accordance with the authority held according to the original instruction given by the constitution, which wants the implementation of elections that are sovereign and carried out on a direct, public, free, confidential, honest and fair basis.